Proceedings of the 28th ACM International Conference on Multimedia 2020
DOI: 10.1145/3394171.3413582
|View full text |Cite
|
Sign up to set email alerts
|

Look, Read and Feel: Benchmarking Ads Understanding with Multimodal Multitask Learning

Abstract: Given the massive market of advertising and the sharply increasing online multimedia content (such as videos), it is now fashionable to promote advertisements (ads) together with the multimedia content. However, manually finding relevant ads to match the provided content is labor-intensive, and hence some automatic advertising techniques are developed. Since ads are usually hard to understand only according to its visual appearance due to the contained visual metaphor, some other modalities, such as the contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In a similar fashion, participants in the current study have explained that some advertisements they had exposed to were creative and enjoyable. Previous studies reported that creative advertisement content was thought-provoking (Vedula, et al, 2017;Zhang et al, 2019). YouTube presents moving images to a wide audience and has established itself as one of the most successful and most visited online video-sharing services (Snelson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar fashion, participants in the current study have explained that some advertisements they had exposed to were creative and enjoyable. Previous studies reported that creative advertisement content was thought-provoking (Vedula, et al, 2017;Zhang et al, 2019). YouTube presents moving images to a wide audience and has established itself as one of the most successful and most visited online video-sharing services (Snelson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [12], Ali et al [1], Wei et al [74] have performed affective multiclass classification on images collected from popular websites. Pilli et al [57], Hussain et al [26], and Zhang et al [82] studied predicting sentiments in image advertisements. Vedula et al [70] extended this idea and developed an advertisement recommendation system using sentiments in advertisement content.…”
Section: Affective Analysis Of Multimedia Contentmentioning
confidence: 99%
“…Therefore, many applications have been developed to support this combination. These applications include fashion products retrieval from videos [30], contextual ads insertion [45,162], etc. We term them Video-to-Retail (V2R) applications.…”
Section: Introductionmentioning
confidence: 99%